Pubertal induction in Turner syndrome without gonadal function: A possibility of earlier, lower-dose estrogen therapy - Hasegawa, Yukihiro; Hasegawa, Tomonobu; Satoh, Mari; Ikegawa, Kento; Itonaga, Tomoyo; Mitani-Konno, Marie; Kawai, Masanobu (Frontiers in Endocrinology, 2023)
Delayed and absent puberty and infertility in Turner syndrome (TS) are caused by primary hypogonadism. A majority of patients with TS who are followed at hospitals during childhood will not experience regular menstruation. In fact, almost all patients with TS need estrogen replacement therapy (ERT) before they are young adults. ERT in TS is administered empirically. However, some practical issues concerning puberty induction in TS require clarification, such as how early to start ERT. The present monograph aims to review current pubertal induction therapies for TS without endogenous estrogen production and suggests a new therapeutic approach using a transdermal estradiol patch that mimics incremental increases in circulating, physiological estradiol. Although evidence supporting this approach is still scarce, pubertal induction with earlier, lower-dose estrogen therapy more closely approximates endogenous estradiol secretion.